(untitled) (Journal of the Bangladesh Agricultural University, 2010)
A study was carried out at four thanas namely, Mymensingh sadar, Muktaghacha, Trishal, and Bhaluka of Mymensingh district to assess impact of BRAC and PDBF sponsored homestead vegetable programme on household income and socio-economic development of rural women. A total of 40 women were involved in vegetable programme as 20 under each BARC and PDBF sponsored households. Purposive sampling technique was followed to select the samples of the study. Vegetable enterprise under both BRAC and PDBF had positive impact on increasing household income. Per household gross margin of vegetable production under BRAC (Tk 1864) was slightly higher than PDBF households (Tk 1745). But per ‘Taka’ return from vegetable under PDBF households (3.86) was higher than that of BRAC households (3.71). Women’s age and education, family land ownership, total number of family members and also number of earning members had significant positive impact on household income. Except marketing, women performed all other activities required for growing vegetables and thus contributed to family income. Vegetable enterprise created an employment for women as they utilized a total of 252 hours year-1 in both PDBF and BRAC households in different activities needed for it. Collection of good seeds and unsatisfactory prices of seeds are the major problems of growing vegetables. Key words: BRAC; PDBF; Homestead vegetable programme; Household income; Socio-economic development; Rural women DOI: 10.3329/jbau.v6i2.4843 J. Bangladesh Agril. Univ. 6(2): 423-428, 2008